Public Organizations of Tatar Students in the Ottoman Empire in the Beginning of 20th Century - Fazliev, Aivaz M.; Shakurov, Farit N.; Minnullin, Zavdat S.; Nafikov, Ilsur Z. (Journal of History Culture and Art Research, 2018)
Impetuous and turbulent flow of the national life of the Tatars in the late XIX - early XX centuries are traditionally associated with the formation of an ethnic community of a new national type and the turning points of world history. The paper presents the first experience of the systematization of information on public organizations of Russian Tatar students in the Ottoman Empire in the early twentieth century. The study is based on the materials of a valuable, little-researched source - the Tatar periodical press of that time. Organization of youth societies abroad is considered as part of the process of the emergence and development of charitable and other associations representing elements of civil society. Along with the Istanbul societies mentioned in the literature, the organizations of young people in Cairo, Mecca, Medina and Beirut are identified, as far as the sources and content and nature of their activities allowed. The documents illustrating the attempts of state structures to resist the training of Muslim youth abroad and their interest in the activities of the respective societies are given. The role of foreign charitable societies and compatriots of Tatar students as a special social institution has been determined. The findings, the factual material of the paper can be used to write general and special works on the history of Turkey, Russia and Tatarstan, the Tatars and other Turkic peoples.